﻿Osteosklerotisch wachsendes Meningeom des Os frontale - Schrum, Anna; Coras, Roland; Andresen, Reimer (Osteologie, 2019)
Menigiomas are counted among the most common benign intracranial tumors. The majority presents with intracranial-directed growth adjacent to the dura mater. Extradural menigiomas are rare and manifest mostly in bone tissue. A dural component is possible. Most of these entities show osteoblastic growth. Osteolytic and combined forms have also been documented. We report the case of a 76 year old female patient with an incidentally found osteosclerotic tumor of the os frontale. A biopsy was performed to rule out malignancy. The histological result showed a rare primarily intraosseous menigioma.
CRIS-Team Scopus Importer:2019-06-04
Keywords: cranium; meningiomas; osteoblastic bone tumors